I-EVALUATE: An Employee Performance Evaluation System with Data Analytics for King’s College of the Philippines-Benguet - Rogelio Luis Guisdan (Southeast Asian Journal of Science and Technology, 2025)
This study addressed the inefficiencies of the traditional faculty evaluation process at King’s College of the Philippines–Benguet by developing a web-based evaluation system called i-Evaluate. The system was designed to modernize data collection, enhance accuracy, and support informed decision-making through real-time analytics. Using Extreme Programming (XP) as the development methodology, the study identified essential information requirements and implemented core features such as self, peer, student, and supervisor evaluations. The usability of the system was assessed using the System Usability Scale (SUS), which yielded an average score of 85.01, indicating high user acceptance and satisfaction. The findings demonstrate that the i-Evaluate system effectively streamlines faculty evaluations, improves efficiency, and supports the operational needs of the Human Resource Management Office.